2022
DOI: 10.1155/2022/2124876
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus pentosus Alleviates Lipopolysaccharide-Induced Neuronal Pyroptosis via Promoting BIRC3-Mediated Inactivation of NLRC4

Abstract: Objective. Neurodegenerative disease is a common neurodegenerative disorder. Lactobacillus pentosus (L. pentosus) plays a neuron-protective role. This study aimed to investigate the effects of L. pentosus on neurodegenerative diseases. Methods. Cells were treated with lipopolysaccharide (LPS) to establish neurodegenerative diseases model in vivo and with L. pentosus strain S-PT84. Reverse transcription-quantitative PCR (RT-qPCR) was applied to determine mRNA levels. Western blot was performed to detect protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Among these genes, YWAHZ and BIRC3 were most heavily weighted in the hazard model. It was suggested that overexpression of YWAHZ and BIRC3 could inhibit the pyroptosis [20,21] . Pyroptosis is a pro-in ammatory cell death, which could be triggered by proin ammatory factors, including Interleukin-1β (IL-1β),IL-6 [22] .During pyroptosis process, the GSDMD was cleaved by the in ammatory caspases in the tumor, which played important roles in the pyroptosis [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, YWAHZ and BIRC3 were most heavily weighted in the hazard model. It was suggested that overexpression of YWAHZ and BIRC3 could inhibit the pyroptosis [20,21] . Pyroptosis is a pro-in ammatory cell death, which could be triggered by proin ammatory factors, including Interleukin-1β (IL-1β),IL-6 [22] .During pyroptosis process, the GSDMD was cleaved by the in ammatory caspases in the tumor, which played important roles in the pyroptosis [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports that Birc3 expression is associated with tumor prognosis, inflammatory response and immune disorders ( 27 29 ). Birc3 inhibits cellular pyroptosis by inactivating NLRC4 inflammatory vesicles ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…To isolate pyroptosis, we treated cells with LPS, flagellin, or a mixture of LPS and nigericin. [40][41][42][43][44][45] To isolate apoptosis, we treated cells with hydrogen peroxide (H2O2) and thapsigargin. 44,[46][47][48][49] In addition, we also incubated some wells with apoptotic and pyroptotic inhibitors prior to treatment.…”
Section: Experimental Design and Cell Death Process Validationmentioning
confidence: 99%